Cannabinoid Regulation of Brain Reward Processing with an Emphasis on the Role of CB1 Receptors: A Step Back into the Future - Panagis, George; Mackey, Brian; Vlachou, Styliani (Frontiers in Psychiatry, 2014)
Over the last decades the endocannabinoid system has been implicated in a large variety of functions, including a crucial modulation of brain reward circuits and the regulation of motivational processes. Importantly, behavioural studies have shown that cannabinoid compounds activate brain reward mechanisms and circuits in a similar manner to other drugs of abuse, such as nicotine, alcohol, cocaine and heroin, although the conditions under which cannabinoids exert their rewarding effects may be more limited. Furthermore, there is evidence on the involvement of the endocannabinoid system in the regulation of cue- and drug-induced relapsing phenomena in animal models. The aim of this review is to briefly present the available data obtained using diverse behavioural experimental approaches in experimental animals, namely, the intracranial self-stimulation paradigm, the self-administration procedure, the conditioned place preference procedure and the reinstatement of drug-seeking behaviour procedure, to provide a comprehensive picture of the current status of what is known about the endocannabinoid system mechanisms that underlie modification of brain reward processes. Emphasis is placed on the effects of cannabinoid 1 (CB1) receptor agonists, antagonists and endocannabinoid modulators. Further, the role of CB1 receptors in reward processes is investigated through presentation of respective genetic ablation studies in mice. The vast majority of studies in the existing literature suggests that the endocannabinoid system plays a major role in modulating motivation and reward processes. However, much remains to be done before we fully understand these interactions. Further research in the future will shed more light on these processes and, thus, could lead to the development of potential pharmacotherapies designed to treat reward-dysfunction related disorders.